2014
DOI: 10.5433/1679-0359.2014v35n6p3173
|View full text |Cite
|
Sign up to set email alerts
|

In vitro ovicidal and larvicidal activity of condensed tannins on gastrointestinal nematode infestations in sheep (Ovis aries)

Abstract: Infestations of gastrointestinal parasitic nematodes in sheep result in significant costs to farmers. These infestations are controlled using synthetic anthelmintic treatments, which can result in the development of anthelmintic resistance in nematodes. The use of plants rich in condensed tannins (CTs) is a promising alternative for controlling infestations of harmful parasites in sheep, and could allow reduction of the chemical products used. This study investigated the in vitro effect of CTs from Acacia mear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 20 publications
2
9
0
1
Order By: Relevance
“…Similar effect was observed with Melaleuca alternifolia, which at a concentration of 56mg/mL and 3.5mg/mL inhibited 88% larval migration and 100% hatchability of H. contortus, respectively (GRANDO et al, 2016). The concentration required to inhibit larval migration is higher than that needed to inhibit hatchability (GRANDO et al, 2016;YOSHIHARA et al, 2014;QI et al, 2015). This is probably due to the fact that infecting larvae can survive in the environment exposed for long periods to deleterious weathering.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Similar effect was observed with Melaleuca alternifolia, which at a concentration of 56mg/mL and 3.5mg/mL inhibited 88% larval migration and 100% hatchability of H. contortus, respectively (GRANDO et al, 2016). The concentration required to inhibit larval migration is higher than that needed to inhibit hatchability (GRANDO et al, 2016;YOSHIHARA et al, 2014;QI et al, 2015). This is probably due to the fact that infecting larvae can survive in the environment exposed for long periods to deleterious weathering.…”
Section: Discussionsupporting
confidence: 63%
“…In recent years, studies involving plants have stood out among the lines of research that seek alternative methods to control ruminant parasites. These studies have revealed promising anthelmintic activity on gastrointestinal parasites of sheep (CAMURCA-VASCONCELOS et al, 2007;YOSHIHARA et al, 2014;RIBEIRO et al, 2014;MARIE-MAGDELEINE et al, 2014;MACEDO et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the larval migration inhibition test (LMI), the 9.4 mg/mL concentration obtained 63.7% efficacy; a similar study carried out by Yoshihara et al (2014), who tested condensed tannins extracted from Acacia mearnsii, found that the 12.5 mg/mL concentration showed 56.3% inhibition, and only reaching 97.1% at the highest concentration used -100 mg/mL, thus demonstrating that better results can be obtained with a concentration increase. When analyzing the results of A. graveolens essential oil action in the different H. contortus development phases, L3 was found to be the most resistant, which can be attributed to the presence of the double cuticle at this larval stage as well as to the lower metabolic activity that occurs at this stage, a fact which was also mentioned by Amarante et al (2014).…”
Section: Discussionmentioning
confidence: 90%
“…1) (Botha et al, 1978;Botha et al, 1981;Drewes et al, 1967;Drewes and Roux, 1963;Hundt and Roux, 1978;Hundt and Roux, 1982;Roux and Maihs, 1960;Saayman and Roux, 1965;Viviers et al, 1983). In addition to technological applications, these compounds also exhibit interesting biological properties such as antioxidant (Olajuyigbe and Afolayan, 2011b;Shen et al, 2010), antitumor (Shen et al, 2010), antimicrobial (Olajuyigbe and Afolayan, 2011a;Olajuyigbe and Afolayan, 2012b), bacteriostatic (Olajuyigbe and Afolayan, 2012ab) and anti-inflammatory (Yoshihara et al, 2014). Yoshihara et al (2014) investigated the effect of PAC from Black Wattle on eclosion eggs and larvae mortality.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to technological applications, these compounds also exhibit interesting biological properties such as antioxidant (Olajuyigbe and Afolayan, 2011b;Shen et al, 2010), antitumor (Shen et al, 2010), antimicrobial (Olajuyigbe and Afolayan, 2011a;Olajuyigbe and Afolayan, 2012b), bacteriostatic (Olajuyigbe and Afolayan, 2012ab) and anti-inflammatory (Yoshihara et al, 2014). Yoshihara et al (2014) investigated the effect of PAC from Black Wattle on eclosion eggs and larvae mortality. Gastrointestinal parasitism in sheep causes numerous losses to farmers.…”
Section: Introductionmentioning
confidence: 99%